Factors Associated with Treatment Compliance among Hypertension Patients - Miniarti Miniarti; Aila Karyus; Bambang Setiaji; Dewi Rahayu; Dian Utama Pratiwi Putri (Knowledge Dynamics, 2025)
Background: Hypertension, often referred to as a “silent killer,” is a major health problem because it frequently presents without symptoms. Poor adherence to antihypertensive treatment can lead to uncontrolled blood pressure, resulting in complications and damage to vital organs. This study aimed to identify factors associated with treatment compliance among hypertension patients in Pesisir Barat Regency in 2025. Methods: This quantitative research employed a cross-sectional design with data collected through questionnaires. The study involved hypertension patients aged 45–70 years and was conducted from February 20 to March 22, 2025. Data included demographic characteristics and factors related to treatment compliance. Bivariate analysis was conducted using the chi-square test, while multivariate analysis was performed using multiple logistic regression. Results: The duration of hypertension was not significantly associated with treatment compliance (p = 0.080). In contrast, significant associations were found with knowledge about hypertension (p = 0.000), motivation to seek treatment (p = 0.000), family support (p = 0.002), role of health workers (p = 0.000), accessibility of health services (p = 0.001), family history of hypertension (p = 0.008), and treatment history (p = 0.005). Conclusion: Several factors were identified as significantly influencing treatment compliance, with the role of health workers emerging as the most dominant factor. Strengthening the role of health workers, alongside family-based interventions and improved access to health services, is recommended to enhance treatment compliance among hypertension patients.